Analysis of Implementation Project-Based Learning in Educational Exhibition Course of the Educational Technology - Khaerat, Andi Ummul (Jurnal Komunikasi Pendidikan, 2025)
This study examines how project-based learning is used in Makassar State University's Educational Exhibition course for the Educational Technology Study Program. The purpose of this study is to outline the phases of project-based learning in the Educational Exhibition course, along with its benefits and drawbacks. The research method used a descriptive qualitative approach with a single case study type on the educational exhibition course. The findings demonstrated that there are multiple steps involved in implementing project-based learning in educational exhibition courses: determining the fundamental questions, project planning, scheduling, monitoring project progress, assessing results or project presentations, and the final stage of experience evaluation. Other research findings indicate that project-based learning in this course provides several benefits for students, such as active participation in the learning process, the ability to integrate theory and practice, team learning and collaboration, as well as the development and enhancement of students' skills. However, a number of issues that need to be addressed, such as uneven student contributions, lack of open communication, and time management problems, can make the educational exhibition project less successful. The findings support designing effective project-based learning programs that meet workforce demands and enhance student's interpersonal skills through authentic experiences.